DIAMBANG KEMUNDURAN DAN KEHANCURAN DINASTY BANI UMAYYAH - Nelly yusra (Lembaga penelitian dan Pengabdian kepada Masyrakat, 2012)
Umayyad dynasty is one of the Khilafah Islamiyah well known throughout the history of Islam in the world. A major role and influence on the development and advancement of Islam recognized by the facts of history. Dynasty is so strong and authoritative, so anyone who sees it will argue that the effort to oust him is something that is not easy. Great progress and success has carved Ummaids trip on the world stage of Islamic history. The successful expansion into some areas in both the east and the west, causing the Islamic empire in the reign of the Umayyad dynasty really very broad. Those regions include Spain, North Africa, Syria, Palestine, the Arabian Peninsula, Iraq, parts of Asia minor, Persia, Afghanistan, the area now called Pakistan, Rurkmenia, Uzbek and Kyrgyz (in CentralAsia).In addition to the expansion of Islamic rule, the Umayyads also widely credited with the development in various fields. First mosques built in the Arabian peninsula. Umayyad dynasty. Cathedral of St. John of Damascus converted into mosques. In al-Qudds (Jerusssalem) ‘Abd al-Malik built the mosque Aqso.Monumen best left today to future generations ialab Qubbah-Sakhr (Dome of the Rock) in which the history of Prophet Ibrahim and Prophet Ismail slaughter began mi ‘raj to the sky. Cardova mosque was also built at this time. While the mosques of Mecca and Medina repaired and enlarged by ‘Abd al-Malik and Walid. Apart from the mosques, also founded the Umayyad dynasty palaces for a place to rest in the desert, like Qusayr Amrah and Musatto the scars are still there today. Ummaids successes are motivated by an appreciation of science and scholars. Yet it is a law of nature nothing is eternal in this world. Strong Dinasty Ummayyah Bani finally experienced periods of decline and destruction. This is what will be discussed in this simple paper.